Assessment of Alpha-Decay Products and Their Correlation with Lung Cancer Risk in Some Selected Districts in the Kurdistan Region, Iraq (Oil & Gas Block) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2026)
This study is investigating the relation between the soil sample alpha-decay and lung cancer risk from selected districts in the Garmian zone, Kurdistan region, Iraq. The presence of the oil and gas blocks is due to the geological properties of the zone. Also, the formation of the zone consists of the lower Fars that contain naturally occurring radioactive materials in the environment. The samples were collected from 41 locations across 27 districts, the samples were prepared and analyzed by an alpha spectrometer to determine the alpha decay activity concentration. The results define that the activity ranged from 4.19 Bq/m3 to 179 Bq/m3 with an average of 32.4 Bq/m3. The lung cancer cases per year per million people range from 2- 37 cases. This article determines the importance of analyzing soil radioactivity as a factor in the environment to the health risk. This research results underscore the need for more studies to improve the effectiveness of the alpha- decay from natural radionuclides to inform the risk that is associated with public health.